THE IMPORTANCE OF HUMAN RESOURCE IN ORGANIZATIONAL DEVELOPMENT (Third Sector Social Economic Review, 2015)
Human resources and the management of human resources are one of the issues on which the organizations aiming to develop emphasize. All the organizations agree on how much human factor is important in organizational world. Thus, the organizations that would like to develop dmit that the most important investment is the invesment in human and accelerate their action in this field. The organizations which have effective, successful and productive human resources can take actions to develop organizations by adopting influencial policies against rapid changes. At this point, employees should be qualified and also have some high-class trainings in order to advance their level. Besides these, the importance of wellprepared training programmes and also the importance of factors motivating employees in development of human resorces are mentioned. Aim of the article is to emphasize the importance of human resources in organizational development. It is ordered as organizational development, organizational change, human resources and comments are stated in the conclusion.
Keywords: Human Resources; OrganizationalChange; Organizational Development